Restricting the construction of second homes in tourist destinations: An effective intervention towards sustainability? - Luzius Stricker (Swiss Journal of Economics and Statistics, 2022)
This study evaluates the impact of the second home restriction (Lex Weber) on construction investments in Switzerland. Different specifications and variations are defined, and the changes in investment behaviour are analysed. A first basic model considers the variation in investments through a discrete event study analysis, while a second model includes a continuous treatment variable to account for the different strong impacts of the law in various municipalities. In the second step, these two basic models are developed in a way that allows to include controls for the different cantonal legislation. The results show that with a delay of three years (due to the expiration of permits), the law had the desired impact on new construction investments. Additionally, the importance of the changes on different outcomes in the local economy and tourism industry are discussed.
Keywords: C23; D72; E22; L74; O18; Z38; 330; Construction; Housing investments; Second homes; Switzerland; Tourism development